Axial Fan Performance under the Influence of a Uniform Ambient Flow Field - Till Heinemann; Stefan Becker (International Journal of Rotating Machinery)
In their application to air-cooled condensers, axial fans are often subject to the detrimental influence of ambient flow fields at their inlet or outlet. While effects have been investigated mostly under perpendicular cross-flow conditions on fans operating as part of an array in their target design point, this study aims at examining the integral influence of uniform ambient flow fields on a single axial fan over a wide operating range. For this purpose, a wind tunnel fan test rig has been designed and assessed. Multiple angles between uniform ambient flow field and fan axis are examined in their integral influence on the characteristic curve of two distinct industrial axial fans with varying inlet modifications. Increasingly with the fan flow rate, perpendicular inlet cross-flow was found to always have a detrimental influence on fan performance. The straight bladed fan reacted less sensitively than the forward skewed fan, and the adverse cross-flow influence could be reduced with an inlet guard grille and with short conical shroud extensions. Cross-flow at the fan outlet showed potential static fan pressure increases at low flow rates.